Development of Tenun Ikat Troso Industrial Center as a Tourist Village in the District of Jepara - Asshofi, Izza Ulumuddin Ahmad; Mukti, Artin Bayu (E-Journal of Tourism, 2018)
Troso is a village that was developed by the government of the district of Jepara to be a tourist village. It has the potential of home-based crafts such as weaving which could be developed into industrial centers. However, not all community members realize the potential. The community members don?t recognize that Troso is going to be developed as a tourist village. On the other hand, the way the community member doing their business is very ineffective. There is no coordination with other businessmen to accommodate and to control the business. Each entrepreneur is working on their tradition to enrich their own business. One entrepreneur to another is a competitor. For these reasons, the village needs to be developed in order to be efficient for the welfare of all people in Troso. Purpose of this research is to understand the existence of Tenun Ikat Troso industrial center and to evaluate development strategy of Tenun Ikat Troso industrial center as a tourist village in the district of Jepara. SWOT. The results show that (i) Strength – Opportunity strategy was focusing on digging deeper of the potency and then wrap them up in a specific brand which will impact on economic sector, (ii) Strength – Threat strategy was focusing on offering the potency of the village to investor to create added value of the village to attract tourists, (iii) Weakness – Opportunity strategy was focusing on building the community awareness of a tourist village plan and the importance of Troso weaving industry association, and (iv). Weakness – Threat strategy was focusing on identifying existing weaknesses of the Troso tourist village and then inviting other stakeholders to get involved in developing the village. Keywords: development; tenun ikat Troso; tourist village